Ontogeny of the skull of the black caiman (Melanosuchus niger) (crocodylia: Alligatoridae) - Vieira, Lucélia Gonçalves; Santos, A. L.Q.; Hirano, L. Q.L.; Menezes-Reis, L. T.; Mendonça, J. S. [UNESP]; Sebben, A. (Canadian Science Publishing, 2019)
We describe the formation of the chondrocranium and the ossification pattern of the skull of the Black Caiman (Melanosuchus niger (Spix, 1825)). The embryos were cleared and double-stained with Alizarin Red S and Alcian Blue 8GX. Additionally, they were visualized by histological hematoxylin and eosin staining and computed tomography imaging. The chondrocranium of M. niger comprised the nasal capsule, orbitotemporal, and optic–occipital regions. Its development began at stage 9, with the chondrification of the acrochordal cartilage, trabeculae, and mandibular cartilage. The optic capsule was formed in the caudolateral portion of the chondrocranium at stage 13. The basal plate appeared at stage 14, with foramina for the hypoglossal. The chondrocranium was completely formed at stage 16. The first osteogenic events were noted at stage 13, in the bones, maxilla, jugal, postorbital, and pterygoid. The quadratojugal, prefrontal, frontal, and squamosal began their ossification at stage 14. The parietal bone began to ossify only at stage 20. The basisphenoid began at stage 15 and the parasphenoid began at stage 16. The jaw bones ossified between stages 13 and 16. The dermal elements started their ossification prior to the endochondral bones.
Keywords: Black Caiman; Chondrocranium; Embryo; Melanosuchus niger; Ossification